The Probability of a Trade at the Ask: An Examination of Interday and Intraday Behavior - Porter, David C. (Journal of Financial and Quantitative Analysis, 1992)
This paper tests the null hypothesis of no difference in the probability of a trade occurring at the ask using a new database containing intraday bid-ask quotes and transaction prices on both U.S. and Canadian Exchanges. We use LOGIT analysis to test the hypothesis across days of the week, price-stratified portfolios, and times of the day. We find systematic patterns in the probability of a trade at the ask resembling previously documented returns anomalies and conclude that the findings of previous weekend and intraday returns studies may be overstated. The significance of this conclusion substantially increases as one moves from the use of interday to intraday data.